The home bias in equities and distribution costs - Philipp Harms; Mathias Hoffmann; Christina Ortseifer (Deutsche Bundesbank, 2010)
We show that including distribution costs into a general equilibrium model of international portfolio choice contributes to explaining the 'home bias' in international equity investment. Our model is able to replicate observed investment positions for a wide range of parameter values, even if agents have an incentive to hedge labor income risk by purchasing foreign equity. This is because the existence of a retail sector affects both the correlation of domestic returns with the domestic price level and the correlation between financial and nonfinancial income.
Keywords: F41; G11; G15; 330; International Financial Market Integration; International Risk Sharing; Home Bias; Internationaler Finanzmarkt; Portfolio-Management; Home Bias Puzzle; Vertriebskosten; Allgemeines Gleichgewicht; Theorie